2013
DOI: 10.1007/s13165-013-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of organic pig farms in selected European countries and their possible influence on litter size and piglet mortality

Abstract: Better knowledge of piglet losses around birth and during lactation, and the role of litter size, housing and management characteristics, should help to identify critical points and hence to improve the situation in organic pig farms. For this purpose, a project was initiated in five EU countries collecting interview data, measures of animal and housing characteristics and production records. This paper presents results regarding production characteristics from 82 herds. Among them, 42 farms were included in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…This survey confirms the findings of others, that organic dairy farming in Europe is largely constituted by small-scale family farms (Sanders et al, 2016). A similar trend was found by Prunier et al (2013) for organic pig farms. Resource demands (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This survey confirms the findings of others, that organic dairy farming in Europe is largely constituted by small-scale family farms (Sanders et al, 2016). A similar trend was found by Prunier et al (2013) for organic pig farms. Resource demands (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…In Stage 1, 114 farm structure variables were entered into an Excel-matrix and screened for missing and abnormal values using procedures exemplified by Prunier et al (2013) and De Boyer des Roches et al (2016) in studies linking animal health outcomes to structural factors. Approximately 20% of the variables were transformed into binary scales using the median as the status threshold.…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%
“…Emissions originating from the sows are allocated to their offspring, and, therefore, higher litter sizes may be regarded as beneficial if all piglets survive and grow adequately. However, in light of the effect of litter size on piglet mortality [20], the focus should be on an adequate litter size, with robust and viable piglets. This suggestion fits to the number of piglets weaned per sow and year being negatively associated with all environmental impact indicators, which may indicate that farms with good management and productivity are at an advantage.…”
Section: Factors Influencing the Environmental Impactsmentioning
confidence: 99%
“…However, it has recently been shown that organic pig farms in Europe can clearly be distinguished into three main "husbandry systems": Pigs may be kept completely outdoors in paddocks on pasture, as in most UK and Italian farms, or indoors, with access to a limited concrete outside run, as in most farms in German speaking countries. Furthermore, both systems, indoor and outdoor, may be combined on one farm for different production stages or during different seasons, as is common, for example, in Denmark or France [1,20].…”
Section: Introductionmentioning
confidence: 99%
“…High forage systems adopted by organic goat producers also present a challenge for an integrated nutrient supply and reproductive synchronization (which is essential for the ruminants' production and health), leading to a relatively stable production level over time [63]. Taking into account the fact that animals reared under extensive conditions expend more energy and tend to produce less, such as the organic pigs studied by Prunier et al [64], the use of feed additives that "naturally" improve feed efficiency would often help. This could also be applied to more intensified organic farms such as many organic dairy farms.…”
Section: The Benefit Of Using Feed Supplements: Why the Feed Industrymentioning
confidence: 99%